Creating a Web-Based Application for Kredit Sales and Insurance at PT Pos Indonesia Cimahi Office - Dewi Sri Rusmayanti (Ebiz Prima Nusa, 2023)
PT Pos Indonesia is one of the State-Owned Enterprises (BUMN), which serves in expedition services to send letters, money, or packages. Currently, PT Pos Indonesia already has a wide range of businesses, one of which is located in Cimahi or the Cimahi Post Office. In advancing its business, the Sales Section of the Cimahi Post Office cooperates with various companies and is responsible for managing credit sales activities and corporate partnerships. One activity is to record kredit sales and partner insurance data. However, in these activities, several obstacles were found, resulting in data reporting delays. Therefore, in this final project, a web-based Data Management Application was created, named SIBAPEN Pos Cimahi. SIBAPEN is a web-based data management application specifically for the Sales Section of the Cimahi Post Office to manage data on sales of credit and insurance sales for partners. The use of SIBAPEN can be a solution to overcome the obstacles experienced. The process of making this application begins with observing, designing, and making applications using a MySQL database and Sublime text software and testing with Alpha and Beta methods. The test results state that the application can work well, and no errors were found. While the feedback given by the Sales Manager as a form of assessment said, this application can be appropriately used and helps manage data in the Sales Department. Thus, the results of this final project can be used by the Sales Section of the Cimahi Post Office.